First detection of H236S in the infrared region; High Resolution Molecular Spectroscopy, HRMS 2018 - Zamotaeva V. A. Valeriya Aleksandrovna; Bekhtereva E. S. Elena Sergeevna; Gromova O. V. Olga Vasilievna; Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Leroy K. A. Klod Andre; Sydow Ch. Christian; Bauerekker Z. Zigurd (2018, 2018)
Title screen